FAKTOR- FAKTOR YANG BERHUBUNGAN DENGAN KEBERADAAN JENTIK NYAMUK AEDES AEGYPTI - Susmaneli, Herlina; Hidayati, Ummi; Agnesia, Yoana (Media Penelitian dan Pengembangan Kesehatan, 2024)
The existence of Aedes aegypti larvae is evidence of the discovery of a population of Aedes aegypti mosquitoes that influence the occurrence of Dengue Hemorrhagic Fever. The larvae-free rate in Labuh Baru Timur Subdistrict was found to be 85%, which shows that it has not reached the national standard above or equal to 95%. The research aimed to determine the factors related to the presence of Aedes aegypti mosquito larvae in Labuh Baru Timur Subdistrict, the working area of ​​the Payung Sekaki Community Health Center, Pekanbaru City in 2023. This research method was quantitative using Observational Analytical with a cross-sectional design. The research was carried out in February - July 2023. The sampling technique was quota sampling of 100 heads of families. The data analysis used is univariate and bivariate. The results of the research showed that there was a relationship between knowledge, attitudes, eradicating mosquito nests, the color of the water reservoir, the location of the water reservoir, and the role of larva monitoring cadres (Jumantik) with the presence of Aedes aegypti mosquito larvae. It is hoped that the Payung Sekaki Community Health Center can provide KIE (Communication, Information, and Education) to the community regarding Dengue Hemorrhagic Fever (DHF), especially how to prevent the presence of Aedes aegypti mosquito larvae and the involvement of Jumantik Cadres is expected to be more active and effective.